Assessing Dsge Models with Capital Accumulation and Indeterminacy - Khramov, Vadim (IMF Working Papers; Working Paper, 2012)
The simulated results of this paper show that New Keynesian DSGE models with capital accumulation can generate substantial persistencies in the dynamics of the main economic variables, due to the stock nature of capital. Empirical estimates on U.S. data from 1960:I to 2008:I show the response of monetary policy to inflation was almost twice lower than traditionally considered, as capital accumulation creates an additional channel of influence through real interest rates in the production sector. Versions of the model with indeterminacy empirically outperform determinate versions. This paper allows for the reconsideration of previous findings and has significant monetary policy implications.